Pengaruh Daya Tarik Iklan, Celebrity Endorser terhadap Minat Beli melalui Citra Merek Produk pada Pelanggan TikTok Shop sebagai Variabel Intervening - Wahyuni, Anisa Tri; Salim, Emil; Sari, Silvia (Lembaga Yasin AlSys, 2025)
The phenomenon in this study is motivated by the large number of BP 21 students of Universitas Putra Indonesia YPTK Padang who subscribe to products on TikTok Shop. The purpose of this study was to test the effect of advertising appeal, celebrity endorsers, on purchasing interest through product brand image on TikTok Shop customers. Brand image is used to determine how Advertising Appeal, Celebrity Endorser affects Purchase Interest. This study is a type of quantitative research. The data analysis approach uses a questionnaire via a google form link. from a sample of 87 respondents. The data analysis method in this study uses partial lash square with Smart PLS 0.4 software. The findings of the study using a partial test (T-TEST) obtained the following results: Advertising appeal improves brand image on TikTok Shop customers. Celebrity endorsers have a positive and significant effect on brand image on TikTok Shop customers. Advertising appeal has no effect on brand image on TikTok Shop customers. However, advertising appeal functions as a mediator for purchasing interest on TikTok Shop customers, while Brand image mediates purchasing interest on TikTok Shop customers.